Edukasi Pencegahan dan Detoksifikasi Pajanan Pestisida pada Petani Melalui Suplementasi Mikronutrien di Desa Borisallo, Kec. Parangloe, Kab. Gowa - Nasruddin Syam; Arni Isnaini Arfah; Wardiah Hamzah; Irna Diyana Kartika (Jurnal Pengabdian Bidang Kesehatan, 2024)
Increasing food production requires pesticides to eradicate pests and leafhoppers that interfere with the growth of food crops and plantations. Pesticides have a negative impact in the form of disease and poisoning on farmers. Farmers are a work that is mostly carried out by the community in Borisallo Village, Parangloe District, Gowa Regency and is a partner in this service. The problems faced by partners are the lack of preventive counseling caused by pesticide exposure to farmers, the lack of micronutrient supplementation to increase body immunity and detoxification of pesticide exposure poisoning, and the unavailability of PPE in managing pesticides in the form of masks and gloves for farmers. The solutions are: (1) Counseling on the prevention of pesticide exposure to farmers, (2) Providing micronutrient supplementation to increase body immunity and detoxify pesticide toxins, (3) Providing PPE in the form of masks and gloves in spraying pesticides on farmers. The activity was carried out for 4 months with funding from the UMI Waqf Foundation. The results of the implementation of PKM (1) Counseling on the prevention of fertilizer exposure to 15 existing farmers, (2) Then continued with the provision of micronutrients and explanation of other food sources that contain micronutrients around the environment (3) Ended with the provision of PPE in the form of masks and gloves that can be used when managing and spraying pesticides. It is recommended to have thorough and periodic health checks on farmers, technical guidance related to healthy and safe fertilization methods continuously and switch to the use of organic or plant-based pesticides